(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article deals with innovative technologies in the vocational education system, "Innovative educational technologies", the importance of increasing the intellectual potential of teachers of various specialties at retraining and advanced training courses for teachers of higher educational institutions, enriching their worldview, innovative educational technologies.